Equity valuation : Target Corporation - Teles, João Duarte (2022)
This dissertation has as its main objective the valuation of Target Corporation, being its major output the resulting intrinsic value of the company’s stock. To unveil the most appropriate methods to follow and apply in order to obtain this output, a review of the main articles and literature of some of the greatest minds in the finance field was firstly performed. Even though many models were studied and reviewed, only some of them were chosen to execute the valuation, due to its greatest practical applications in “real-life” examples. Resultingly, the first and main method used was the Discounted Cash Flow, which is one if not the most known model to perform valuations. By performing the forecast of the company’s financial statements, it was possible to consequently forecast the free cash flows to the firm, and then achieve the Equity Value. Finally, the fair price of Target’s stock deemed by this model was of $259.83 per share. The second model applied was the Relative Valuation Model. By performing this valuation using P/E, EV/EBITDA, and EV/Sales multiples, intrinsic values of $220.62, $307.28, and $286.09 per share were achieved. The overall conclusion yielded by both these models is that Target’s stock is undervalued, being its intrinsic value greater than its market price. However, the report provided by Morningstar found otherwise, opinionating that its valuations conclude that the stock is overvalued and fairly priced at 159$ per share, being this different fair price the result of different assumptions and report timings.